2021
DOI: 10.3389/fonc.2021.694021
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA LINC00152 Regulates Self-Renewal of Leukemia Stem Cells and Induces Chemo-Resistance in Acute Myeloid Leukemia

Abstract: Relapse of acute myeloid leukemia (AML) has a very poor prognosis and remains a common cause of treatment failure in patients with this disease. AML relapse is partially driven by the chemoresistant nature of leukemia stem cells (LSCs), which remains poorly understood, and our study aimed at elucidating the underlying mechanism. Accumulating evidences show that long noncoding RNAs (lncRNAs) play a crucial role in AML development. Herein, the lncRNA, LINC00152, was identified to be highly expressed in CD34+ LSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The inhibition of LINC00152 increased the sensitivity of leukemic cells to doxorubicin. These results suggest that LINC00152 may serve as a potential prognostic marker in AML patients ( 8 ). Transcriptome analysis has identified LINC00152 as a biomarker for early relapse and mortality in acute lymphoblastic leukemia ( 9 )…”
Section: Function and Mechanisms Of Linc00152 In Human Cancermentioning
confidence: 79%
See 1 more Smart Citation
“…The inhibition of LINC00152 increased the sensitivity of leukemic cells to doxorubicin. These results suggest that LINC00152 may serve as a potential prognostic marker in AML patients ( 8 ). Transcriptome analysis has identified LINC00152 as a biomarker for early relapse and mortality in acute lymphoblastic leukemia ( 9 )…”
Section: Function and Mechanisms Of Linc00152 In Human Cancermentioning
confidence: 79%
“…Cui et al ( 8 ) demonstrated that LINC00152 promotes PARP1 expression, which induces chemoresistance in acute myeloid leukemia and regulates the self-renewal of LSCs ( 8 ). In addition, knockdown of LINC00152 can inhibit PARP1 expression to improve the sensitivity of leukemia cells to chemotherapy, thus improving the prognosis of leukemia patients.…”
Section: The Role and Mechanism Of Linc00152 In Radiotherapy And Chem...mentioning
confidence: 99%
“…Moreover, the expression of LINC00152 was correlated with poly (ADP-ribose) polymerase 1 ( PARP1 ) expression and knockdown of LINC00152 resulted in decreased PARP1 expression which consequently resulted in an increased sensitivity of AML cells to the DNA damaging agent-doxorubicin. Thus, LINC00152 potentially contributes to the chemoresistance of LSCs in AML via upregulating PARP1 [56 ▪ ].…”
Section: Potential Mechanisms Of Lncrnas Conferring Drug Resistance I...mentioning
confidence: 99%
“…Previous studies have revealed that lncRNAs play essential roles in many important regulatory processes, such as transcription regulation, genome imprinting, chromatin modification, and nuclear transport, which have attracted widespread attention ( Groff et al, 2016 ; Long et al, 2017 ). Some lncRNAs, including CASC15 ( Fernando et al, 2017 ), UCA1 ( Li et al, 2020 ), H19 ( Zhang et al, 2018 ), HOTAIRM1 ( Chen et al, 2020 ), LINC00152 ( Cui et al, 2021 ), have been identified to be associated with the recurring mutations, clinical features and prognosis of AML. Accumulating studies have indicated that aberrant expression of certain specific lncRNAs in tumor cells can be used as a diagnostic marker or a potential drug target.…”
Section: Introductionmentioning
confidence: 99%